Sobucalı Mehmet Efendi'nin Keşfü'l-inaye fi mesaili'l-kifaye adlı eserinin inceleme ve tahkiki (edisyon kritik) - Bilin, Abdullah (My University, 2009)
Arap dili Kuran ve sünnetin ana dili olması sebebiyle her zaman önemini korumuştur. Arap dilcileri, grameri iki kısma ayırırlar. Sarf, kelimelerin yapılarını inceleyen ilimdir; nahiv ise cümle bilgisidir. Bu çalışmamızda Osmanlı âlimlerinden İmam Birgivi (v.981/ 1573)’nin Arap gramerine dair yazmış olduğu “Kifâyetü’l-mübtedi”nin şerhlerinden biri olan Sobucalı Mehmed Efendi (v.1161/ 1748)’nin yazmış olduğu “Keşfü’l-inâye fi mesâili’l-Kifâye” isimli eserinin tahkik ve incelemesi yapılmıştır. Çalışmamız üç bölümden oluşmaktadır. Birinci bölümde müellifin hayatı, ilmi şahsiyeti ve eserleri hakkında bilgi verilmiştir. İkinci bölümde sunduğumuz metnin daha iyi anlaşılması için, önce konuya giriş mahiyetinde Kifâyetü’l-mübtedi’den kısaca bahsedilmiş ardından Keşfü’l-inâye fi mesâili’l-Kifâye ayrıntılı olarak incelenmiştir. Üçüncü bölümde ise eserin tahkikli metni verilmiştir.

Arabic language ,which is language of the Holy Quran and hadith has been always important in Islamic world. Arabic gramer is divided two parts by linguists. One of these parts is sarf which is a field of arabic linguistic focuced on the structure of words. The other is nahiv which is a field of arabic linguistics focused on the structure of sentences. In this work, “Keşfü’l-inâye fi mesâili’l-Kifâye” by Sobucalı Mehmed Efendi (v.1161/ 1748), who was one of the commentator of “Kifâyetü’l-mübtedi” on Arabic grammar written by Imam Birgivi, the Ottoman scholar, has been examined and verified. Our study has been formed in three capters. In first chapter, it is focused on the writer’s life, scholarship and literal aspect. In the second chapter, “Keşfü’l-inâye fi mesâili’l-Kifâye” is investigated and as an introduction, Kifâyetü’l-mübtedî are taken into hand and then the study of Sobucalı Mehmed Efendi is examined in details in order to illuminate him. In the third chapter of the study, the Arabic text which is paged right to left the verifying text of “Keşfü’l-inâye fi mesâili’l-Kifâye” is placed
Keywords: Arap Dili